Bioinspired reinforcement of cyclosiloxane hybrid polymer. Issue 95 (14th November 2018) - Song, Yujie; Tang, Xiuzhi; Liang, Yen Nan; Lee, Heng Yeong; Liu, Ming; Zhang, Liying; Bi, Shuguang; Mu, Chenzhong; Hu, Xiao
Abstract : Structural analysis showed that cyclosiloxane hybrid polymer (CHP) is a collection of nano-sized nacre-like structures arranged in random orientations and CHP can be reinforced through a bio-inspired method. Abstract : Structural analysis showed that cyclosiloxane hybrid polymer (CHP) is a collection of nano-sized nacre-like structures in random orientations. Inspired by the reinforcement of nacre-like materials, basal-functionalized graphene (GO-AA) was inserted between CHP layers, acting as 'double-sided tape' to improve the mechanical properties. The resulting GO-AA/CHP nanocomposites showed a 156% improvement in toughness with only a 0.08 wt% loading of GO-AA, and a 25% improvement in thermal conductivity with a 0.10 wt% loading of GO-AA. The proposed 'double-sided tape' effect was also used to explain the highly efficient enhancement in thermal conductivity. This research promotes the application of CHP in harsher environments, demonstrates its prospects in thermal management areas, and contributes to nature-inspired materials design.